Integrating Media Literacy into Contemporary Education: A Fundamental Element of the Modern Curriculum - Potnikova, Mariia; Vovchasta, Nataliia; Zelenin, Vsevolod; Hnedko, Natalia; Hetmanenko, Liudmyla (Journal of Posthumanism, 2025)
The growing use of information technology in various fields has created challenges associated with new risks, which has led to an increase in the role of media education in society. Media literacy is an important component of the educational environment, as it provides skills for searching and analysing scientific information. Our study aimed to identify the problems students face when searching for information on the Internet and to determine the impact of media literacy on student learning. The methods used in the study were analysis, synthesis, induction, deduction, survey, statistical comparison, trend method, Student’s t-test for independent samples, and one-factor analysis of variance ANOVA. A survey and testing of 679 students of the 1st, 2nd, 3rd and 4th years of study were conducted. The results of the study showed that the problems of information search by students were dominated by restrictions on access to scientific and metric databases, complexity of search methods, a large number of databases and unreliability of information. Moreover, senior students consider unreliable data an important problem in searching for information on the Internet, related to developing students’ critical thinking in the learning process. Instead, students who had not studied the basics of media literacy considered the complexity of search methods and the large number of scientific and metric databases the main problems. The test results showed better results in understanding media data content among senior students due to the combination of media education and critical thinking skills.